Driyorejo Market Analysis Based on Environmental Health Principles and Supporting Infrastructure - Sumarno, Tiara Indrawati; Syafiuddin, Achmad; Kencana, Eka Mayluna (IJIS Edu : Indonesian Journal of Integrated Science Education, 2022)
The market is a place for public to meet and the occurrence of relationships between individuals, in the market there are various kinds of buying and selling transaction activities and it is also a meeting place for many people so it is very vulnerable to the transmission of various diseases. The Driyorejo Market which is located in the Driyorejo District area is not included in the category of healthy markets that have market sanitation that meets health standards. Purpose of this study aims to describe the level of sanitation at the Driyorejo market in 2022. This research is a quantitative study conducted on March 21, 2022. The focus of the variables studied are location, market building, sanitation, sanitation management, community empowerment and behavior clean and healthy living, security and supporting facilities by utilizing market sanitation inspection instruments. The research results show that 2022 Driyorejo Market Sanitation does not meet the requirements. Driyorejo market sanitation does not meet the health standard requirements of healthy market sanitation.